From rice husk to transparent radiation protection material / Iskandar Shahrim Mustafa... [et al.] - Mustafa, Iskandar Shahrim; Razali, Nur Ain Nabilah; Ibrahim, Abdul Razak; Yahaya, Nor Zakiah; Kamari, Halimah Mohamed (Universiti Teknologi MARA, Perlis, 2016)
High amount of silica (SiO2) content, 99.36% was successfully prepared from Rice Husk Ash (RHA) through the burning of rice husk. Eventually, quaternary glasses were fabricated using melt quenching technique based on chemical compound composition xBi2O3 - (1-x)ZnO - 0.2B2O3 - 0.3(SiO2)RHA. The final thickness of glass samples prepared was within ~3.41mm. As the mole percentages of Bi2O3 increased, the glass density and molar volume was also increased from 4.45 gcm-1 to 6.60 gcm-1. The increment is due to larger atomic number of Bi3+ compared to the Si2+, B3+ and Zn in the glass samples. However, the oxygen packing density decreased as mole percentages of Bi2O3 were increased from 240.44 g-atom/l to 161.24 g-atom/l. The decreasing in oxygen packing density was due to the high non-bridging oxygen in the glass samples. The radiation attenuation parameterization was measured using 241Am as source of gamma ray interactions at energy 59.54 keV. The mass attenuation coefficient increased from 0.53cm2g-1 to 5.12cm2g-1 relatively towards the increment of Bi2O3 mole percentages. The phenomenon is due to the escalating in photoelectric absorption effect and declining in the Compton scattering caused by high atomic number of Bi3+ in the glass samples. Using Lorentz-Lorentz formulation, the refractive index obtained for glass samples prepared was within favourable range from 1.97 to 1.73.